Mouse Model of Spinal Cord Hypoperfusion with Immediate Paralysis Caused by Endovascular Repair of Thoracic Aortic Aneurysm. (30th January 2023) - Kelani, Hesham; Corps, Kara; Mikula, Sarah; Fisher, Lesley C.; Shalaan, Mahmoud T.; Sturgill, Sarah; Ziolo, Mark T.; Abdel-Rasoul, Mahmoud; Basso, D. Michele; Awad, Hamdy
Abstract : Background: A clinically relevant mouse model of thoracic endovascular aortic repair–induced ischemic spinal cord injury has been lacking since the procedure was first employed in 1991. The hypothesis was that ligation of mouse intercostal arteries would simulate thoracic endovascular aortic repair–induced ischemic spinal cord injury and behavioral deficit. The aim was to create a mouse model of thoracic endovascular aortic repair–induced spinal cord hypoperfusion by ligating five pairs of mouse intercostal vessels. Methods: Mice were divided into sham (n = 53) and ligation (n = 60) groups. The procedures called for double ligation of three pairs and single ligation of two pairs of thoracic intercostal arteries in adult C57BL/6 mice. A laser Doppler probe was used in vivo on the spinal cords and intercostal arteries to document the extent of arterial ligation and spinal cord hypoperfusion. The Basso Mouse Scale for Locomotion, histological studies, and electron microscopy demonstrated postligation locomotive and histopathological changes. Results: Ligation induced a significant and instantaneous drop in blood flow in the intercostal arteries (% change; mean = −63.81; 95% CI, −72.28 to −55.34) and the thoracic spinal cord (% change; mean = −68.55; 95% CI, −80.23 to −56.87). Paralysis onset was immediate and of varying degree, with behavioral deficit stratified into three groups: 9.4% exhibited severe paralysis, 37.5% moderate paralysis, and 53.1% mild paralysis at day 1 (n = 32; P < 0.001). Mild and moderate paralysis was transient, gradually improving over time. Severe paralysis showed no improvement and exhibited a higher mortality rate (83%; n = 15 of 18) compared to moderately (33%; n = 6 of 18) and mildly (24%; n = 6 of 25) paralyzed mice ( P < 0.001). The overall ligation group survival rate (84%; n = 46 of 55) was significantly lower than the sham group (100%; n = 48 of 48) with P = 0.003. Conclusions: The mouse model generates reproducible spinal cord hypoperfusion and accompanying histopathological ischemic spinal cord damage. The resulting anatomical changes and variable behavioral deficits mimic the variability in radiological and clinical findings in human patients. Abstract : In mice, double ligation of three pairs alongside single ligation of two pairs of intercostal arteries led to reproducible spinal cord hypoperfusion and to an immediate paralysis of variable severity below the ligation level. The variable degree of deficit and the gradual improvement throughout a 2-week follow-up period in mice mimics the recovery process in humans presenting with spinal cord ischemia after endovascular repair of thoracic aortic aneurysm.